Design of Servo Door Lock System and Home Lighting Based on The Internet of Things - Lasmadi, Lasmadi; Kurniawan, Freddy; Ramdan, Ramdan; Sajati, Haruno (JOURNAL OF ELECTRICAL AND SYSTEM CONTROL ENGINEERING, 2025)
The application of Internet of Things (IoT) technology in home security and comfort systems is constantly evolving. This research proposes the design and implementation of an IoT-based servo door lock system and home lighting control. The system is designed using the Wemos D1 microcontroller, a servo motor, an infrared sensor, a relay, and a light sensor. The results of this study indicate that the system can be effectively implemented and meets the design objectives. Based on tests conducted, users can access the door lock and control home lighting through a mobile or web application. The delay in executing commands from the application to the servo door lock system is approximately 38.93 seconds, while the delay to the relay system is about 34.83 seconds. Furthermore, the infrared and light sensors allow users to monitor the status of the door lock (open/closed) and lighting (on/off) via the application.